Storying leaks for sharing: The case of leaking the "Moscovici draft" on Twitter. (October 2017) - Giaxoglou, Korina
Highlights: Journalistic practices online are studied as networked practices of storying-for-sharing. Breaking news on Twitter unfold both as microstories and as incipient multi-turn stories. Breaking news formats on Twitter feature a concise, portable storyline and cumulative evaluation(s). Sharing a leak online creates participant positions of narrative stancetaking. Abstract: This article proposes a discourse-narrative approach to news making online as a networked practice of storying and sharing. This approach is illustrated in the examination of the release of a draft Eurogroup statement via journalist Paul Mason's Facebook, Scribd and Twitter accounts on the 16th February 2015. The analysis draws on small story insights (Georgakopoulou, 2015a, b, c) and the empirical framework of sharing (Androutsopoulos, 2014). It shows how the release of this leak event on Twitter is storied as a breaking news story unfolding moment-by-moment as it happens, at the same time as making up an incipient record of the event as it happened. It is argued that breaking news (micro)stories are shared as moments of narrative stancetaking, featuring a concise, portable storyline and cumulative evaluation(s) that foreground the relevance of the leak for the ongoing discussions on the Greek bailout negotiations as well as the continued importance of the journalist as the mediator of the leak. In this case of sharing a leaked document with networked participants, narrativity is drawn upon as a key resource for producing and circulating alternative stances on the Greek crisis, creating a range of networked participation positions. This article contributes to the study of news sharing online and digital storytelling based on the qualitative analysis of 'small' data.